AB0083 Antiphospholipid Syndrome and Marcers of Inflamation. (10th June 2014) - Seredavkina, N.; Reshetnyak, T.; Satybaldyeva, M.; Verizhnikova, Z.; Alexandrova, E.; Novikov, A.; Nasonov, E.
Abstract : Background: Last years the reasons of earlier and more frequent atherosclerosis and cardiovascular/cerebrovascular disorders in rheumatic diseases and also the participation of antiphospholipid antibodies (aPL) in atherothrombosis are up for debate. Analysis of blood concentration of deferent autoantibodies, acute-phase reactants and lipid profile as well as investigation of traditional and nontraditional risk factors and intima-media thickness in patient (pts) with antiphospholipid syndrome (APS) is topical for the understanding of the role of atherosclerosis in APS. Objectives: To investigate levels of high sensitive CRP (hs-CRP), interleukin 6 (IL 6), tumor necrosis factor α (TNFα), soluble TNFα-receptor 1 (sTNFα-R1) and intercellular adhesion molecule 1 (ICAM-1) in APS pts. Methods: The total of 96 APS pts (52 with primary APS (PAPS) and 44 with SLE+APS) and 29 age– and sex–matched healthy controls (HC) were included. Thromboses in past history were registered in 83/96 (86%) pts: in 21 – arterial (AT), in 38 – venous (VT), in 24 – AT+VT. Serum markers of inflammation and endothelial cells activation were measured: IL 6 – in 89 pts and 20 HC, TNFα – in 73 pts and 20 HC, sTNFα-R1 – in 90 pts and 28 HC and ICAM-1 – in 66 pts and 20 HC, respectively. All the pts underwent electrocardiography, echocardiography, Holter monitoring, ultrasonography and laboratory testing including aPL, hs-CRP and lipid profile of plasma. Results: Serum levels of hs-CRP, IL 6, TNFα, sTNFα-R1 and ICAM-1 were significantly higher in pts compared to HC (p<0.05 in all cases). Levels of IL 6 and sTNFα-R1 in PAPS pts were lower than in SLE+APS pts (1.01 [0.27; 1.90] pg/ml; 2.43 [1.05; 4.13] ng/ml vs 2.30 [1.90; 3.30] pg/ml; 3.89 [2.20; 6.00] ng/ml respectively, p<0.05). Concentration of ICAM-1 was significantly higher in pts with VT than in pts with AT, with AT+VT and without T (445.2 [342.7; 426.4] vs 316.0 [282.3; 349.4] vs 356.7 [327.2; 383.4] vs 344.1 [314.2; 379.2] ng/ml, respectively; p=0.04). Coronary heart disease (CHD) positively associated with increased levels of sTNFα-R1: CHD was diagnosed in 17/45 pts with elevated sTNFα-R1 levels and in 3/45 pts with normal sTNFα-R1 levels (OR 2.13 [95%IC 1.51; 2.99], p<0.001). During the first year after thrombosis there was an inverse association between postthrombotic time duration (PTTD) and IL 6 and TNFα: increased levels of IL 6 and TNFα were detected in 4/4 (100%) and 8/15 (53%) pts with acute thrombosis (PTTD ≤1 week), in 15/16 (94%) and 5/5 (100%) pts with 1<6 months and in 12/12 (100%) and 19/21 (90%) pts with 6<12, respectively, p<0.05 in all cases. Levels of IL 6 (3.36 [2.33; 4.13] pg/ml) and TNFα (5.75 [3.19; 8.28] ng/ml) in pts with PTTD ≤1 week were higher than in pts with 1<6 months (IL 6 =1.88 [1.14; 4.08] ng/ml and TNFα =4.53 [3.55; 6.81] ng/ml) and 6<12 months (IL 6 =1.72 [1.01; 2.86] pg/ml and TNFα =2.9 [1.96; 3.49] ng/ml), p<0.05 in all cases. Conclusions: Serum levels of hsC-RP, IL 6, TNFα, sTNFα-R1 and ICAM-1 were significantly elevated in pts compared to HC. ICAM-1 level was higher in pts with VT than pts with AT, AT+VT and without T. Increased level of sTNFα-R1 was associated with CHD. During the first year after thrombosis there was an strong inverse association between postthrombotic time duration and IL 6 and TNFα. Increased levels of IL 6 and TNFα are reflective of subclinical inflammation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5737